Effect of premature ejaculation on depression and sexual functions in female partners: A report from Eastern Turkey - Karakeci, A.; Korkmaz, S.; Karakoc, O.; Karakoc, A. A. U.; Firdolas, F.; Pirincci, N. (Wolters Kluwer Medknow Publications, 2019)
Background: Premature ejaculation (PE) is a sexual dysfunction causing female sexual dissatisfaction that eventually leads to poor quality of life in both partners. Aims: To show the presence of depression, anxiety, sexual function disorders and their prevalence in spouses of males with PE living in Eastern Turkey. Materials and Methods: Ninety male patients suffering from PE who referred to the andrology clinic between January 2016 and March 2017 and diagnosed with PE (Acquired Premature ejaculation) according to the DSM-IV criteria and their partners were included in the study. Male patients answered the PE Profile, Arabic Index of PE, PE Diagnostic Tool, and Arizona Sexual Experiences Scale (ASEX) Questionnaires. Spouses of male patients with PE answered the Arizona Sexual Experiences Scale, Beck Depression Inventory, and Beck Anxiety Inventory Questionnaires. SPSS software version 21.0 was used for statistical analysis. Results: Our study revealed a positive correlation between the PE profile and partners' depression levels (P = 0.03). Also, the average ASEX Scale score of the both genders suggest that patients and partners believe they did not have a severe sexual function disorder. Conclusions: PE can cause psychological problems in both males and females. However, reflection of this pathology can vary from one society to another.
Keywords: Depression; premature ejaculation; psychological burden; sexual dysfunction